RANGKAIAN BUNGA PAPAN ANTARA KEINDAHAN DAN LINGKUNGAN SEBAGAI PENDUKUNG PARIWISATA BERKELANJUTAN - Adi, Ida Ayu Sri Puspa; Arthini, Ni Nyoman Suci; Saputra, I Putu Adi (Institut Agama Hindu Negeri Gde Puda Mataram, 2024)
The purpose of this study was to determine the comparison materials of wooden boards and styrofoam in board flowers in the direction of Nusa Dua tourism destinations. The research methods used was interviews and documentation studies, then the data obtained were analyzed using qualitative descriptive methods. This study uses theories from Veronika & Wardaya regarding factors that influence consumer buying interest in environmentally friendly products. Based on this theory, the answer was obtained that flower boards made from wooden boards have advantages in terms of material price, product quality, product quantity and ease of use of products, while for Styrofoam only superior in terms of product distribution. Based on the results of the study, the advice that can be given is, in addition to starting to follow the regulations issued by the government regarding the cessation of the use of Styrofoam, but also contributing to reducing the use of this Styrofoam material, by replacing the material used in flower boards into more environmentally friendly materials such as wooden boards